استثمارالعقار السياحي وعلاقته بالتنمية المستدامة - معيرش عبد الرحيم (جامعة المسيلة, 2025)
Tourism real estate investment is one of the key pillars of sustainable development due to its role in enhancing tourism infrastructure and stimulating economic growth. By establishing and developing tourism facilities such as hotels, resorts, and tourist villages, a favorable environment for local and foreign investments is created, contributing to job creation and supporting tourism-related sectors, such as transportation, services, and trade. This type of investment also improves the quality of life in tourist destinations by developing public facilities and preserving natural and cultural landmarks. To ensure the sustainability of this sector, it is essential to adopt policies that safeguard environmental resources and balance investment requirements with the need to protect the natural and cultural surroundings. This makes tourism real estate a crucial factor in achieving balanced and sustainable economic development.
Keywords: tourism investment; tourism real estate; sustainable development